Functioning, participation, and quality of life in children with intellectual disability: an observational study. (30th August 2020) - Williams, Katrina; Jacoby, Peter; Whitehouse, Andrew; Kim, Rachel; Epstein, Amy; Murphy, Nada; Reid, Sue; Leonard, Helen; Reddihough, Dinah; Downs, Jenny
Abstract : Aims: To investigate associations between functioning, community participation, and quality of life (QoL) and identify whether participation mediates the effects of functioning on QoL. Method: The caregivers of 435 children (211 females, 224 males; mean age 12y; SD 3y 11mo; age range 5–18y) with intellectual disability and autism spectrum disorder, cerebral palsy, Down syndrome, or Rett syndrome reported on their child's functioning (dependence for managing personal needs, mobility, communication, eye contact when speaking), frequency of participation, and QoL. Linear regression and mediation analyses were used to evaluate the relationships between child functioning, participation, and QoL. Results: Children with greater dependency for managing personal needs and limited eye contact when speaking experienced poorer QoL. Less impaired functioning was associated with more frequent participation, which, in turn, was associated with a 3‐point gain in QoL for each additional point in frequency of participation (coefficient=2.67, 95% confidence interval 1.56–3.78). The effect of impaired functioning on QoL was partially mediated by participation in children with greater dependency in managing personal needs and those with mildly impaired communication. Interpretation: Greater levels of impairments with poorer functioning, notably a high level of dependence, were associated with poorer QoL. Poorer QoL can be partly explained by less frequent community participation. Abstract : This article's abstract has been translated into Spanish and Portuguese. Follow the links from the abstract to view the translations. This article is commented on by Alveirinho Correia on page 11 of this issue. Funcionamiento, participación y calidad de vida en niños con discapacidad intelectual: estudio observacional: Objetivo: Investigar las asociaciones entre el funcionamiento, la participación comunitaria y la calidad de vida (CdV) e identificar si la participación media los efectos del funcionamiento en la CdV. Método: Participaron los cuidadores de 435 niños (211 niñas y 224 niños; media de edad 12 años DS 3 años 11 meses; rango de edad 5‐18 años) con discapacidad intelectual y trastorno del espectro autista, parálisis cerebral, síndrome de Down o síndrome de Rett. Informaron sobre el funcionamiento de sus hijos (dependencia para el manejo de necesidades personales, movilidad, comunicación, contacto visual al hablar), frecuencia de participación y calidad de vida. Se realizaron análisis de mediación y regresión lineal para analizar las relaciones entre el funcionamiento, la participación y la calidad de vida de los niños. Resultados: Los niños con mayor dependencia para manejar sus necesidades personales y aquellos con limitado contacto visual al hablar, experimentaron una peor calidad de vida. Un menor compromiso en el funcionamiento se asoció con una participación más frecuente, que, a su vez, se asoció con una ganancia de 3 puntos en la CdV por cada punto adicional en la frecuencia de participación (coeficiente = 2, 67, intervalo de confianza del 95%: 1, 56–3, 78). El efecto del deterioro del funcionamiento sobre la calidad de vida fue mediado parcialmente por la participación en niños con mayor dependencia en el manejo de sus necesidades personales y en aquellos con un compromiso leve en la comunicación. Interpretación: Niveles mayores de deficiencias en el funcionamiento, en particular un alto nivel de dependencia, se asociaron con una peor calidad de vida. La menor calidad de vida se puede explicar, en parte, por una participación comunitaria menos frecuente. Funcionamento, participação e qualidade de vida em crianças com deficiência intelectual: um estudo observacional: Objetivo: Investigar associações entre funcionamento, participação na comunidade, e qualidade de vida (QV), e identificar se a participação media os efeitos do funcionamento na QV. Método: Os cuidadores de 435 crianças (211 do sexo feminino, 224 do sexo masculino; média de idade 12a; DP 3a 11m; variação da idade: 5–18a) com deficiência intelectual e transtorno do espectro autista, paralisia cerebral, síndrome de Down, ou síndrome de Rett, relataram o funcionamento de suas crianças (dependência para manejar necessidades pessoais, mobilidade, comunicação, contato pessoal ao falar), frequência de participação, e QV. Análises de regressão linear e de mediação foram usadas para avaliar as relações entre funcionamento da criança, participação, e QV. Resultados: Crianças com maior dependência para o manejo das necessidades pessoais e contato visual limitado ao falar experimentaram pior QV. Funcionamento menos comprometido foi associado com maior frequência de participação, o que, por sua vez, se associou com um ganho de 3 pontos em QV para cada ponto adicional na frequência de participação (coeficiente=2, 67, intervalo de confiança a 95% 1, 56–3, 78). O efeito do funcionamento deficiente na QV foi parcialmente mediado pela participação em crianças com maior dependência no manejo de necessidades pessoais e naquelas com comunicação levemente comprometida. Interpretação: Maiores níveis de deficiência com pior funcionamento, notavelmente um maior nível de dependência, foram associados com pior QV. Pior QV pode ser parcialmente explicda por uma participação menos frequente na comunidade.